An evaluation of neglected tumors: Giant basal cell carcinomas - Agdogan, Ozgur; Ural, Alper (Annals of Medical Research, 2021)
Aim: Giant basal cell carcinomas (GBCCs) which constitute approximately 1% of basal cell carcinoma are aggressive tumors characterized by deep tissue invasion, high risk of metastasis, and poor prognosis. We aimed to analyze demographics, treatment, and outcome of patients with GBCCs in this study. Material and Methods: Between 2017 and 2020, nine patients applied to Department of Plastic and Reconstructive Surgery and underwent surgical treatment for GBCC were included in the study. Age, sex, localization, tumor size, treatment and comorbid diseases of the patients were reviewed retrospectively.Results: Six patiens were male and three patients were female. The mean age was 68.6 ±3.8 years, ranging from 62 to 78 years. The tumors were located on cheek (n=4), frontotemporal region (n=2), cheek nose lower eyelid junction (n=1), scalp(n=1) and dorsum of the hand (n=1). The largest of the lesions was 8x10 cm and the smallest was 4x6 cm.The defect sizes following tumor removal ranged from 24 to 80cm2 with an average of 43,6 cm2. Nodular GBCC was the most common histological subtype (n=6), followed by superficial (n=2) and morpheaform (n=1). Two patients were skin grafted after excision of GBCC whereas cheek rotation flaps (n=2), cervicofacial flaps (n=3) and pedicled forehead flaps (n=2) were utilized for reconstruction.Conclusion: Since health insurance covers oncologic surgery and there is an extreme ease to reach a health professional in our country, the most common reason to still encounter GBCC seems like negligence. GBCCs are rare, but they need proper interventions when detected. Aggressive surgery should not be avoided for better outcomes.
Keywords: Basal cell cancer; malignant neoplasms neglected diseases; reconstructive surgery